2019
DOI: 10.26618/exposure.v8i2.2799
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Writing Error in Using English Causative

Abstract: This research aimed to find out kinds of errors in the use of active and passive English causative in writing is made by the sixth-semester Students English Department at the Muhammadiyah University of Makassar. The method of this research was a correlation with the descriptive quantitative method. The instrument of this research was the writing test. This research took population was the sixth-semester students of English Department at Makassar Muhammadiyah University. This research used the random sampling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In the fourth sentence, the author's sentence seems incoherent because not everything mentioned in the previous sentence is explained. This is similar with the research findings found by Chen (2011) and Nawir & Nappu (2019). The fourth sentence reads that human life is faced with various events, challenges, obstacles, opportunities, and experiences, so coherently, the author should write that in fighting for happiness, goodness, and greed, humans will be faced with various events, challenges, and obstacles.…”
Section: Resultssupporting
confidence: 81%
“…In the fourth sentence, the author's sentence seems incoherent because not everything mentioned in the previous sentence is explained. This is similar with the research findings found by Chen (2011) and Nawir & Nappu (2019). The fourth sentence reads that human life is faced with various events, challenges, obstacles, opportunities, and experiences, so coherently, the author should write that in fighting for happiness, goodness, and greed, humans will be faced with various events, challenges, and obstacles.…”
Section: Resultssupporting
confidence: 81%